Relationship between internal and external load metrics in professional male basketball players - Cabarkapa, D. V.; Cabarkapa, D.; Eserhaut, D. A.; Fry, A. C. (Journal of Human Sport & Exercise, 2023)
Quantifying both external and internal training loads that athletes are exposed to during training sessions is often recommended to assess multifactorial sport-specific demands. Thus, the purpose of the present study was to determine the relationship between a widely used subjective marker of internal load (rate of perceived exertion - RPE) and external load variables obtained from an innovative inertial measurement unit (IMU) device within a cohort of professional male basketball players. Twenty-one athletes competing in the first- and second-tier national basketball leagues in Europe wore an IMU device (i.e., VertTM) during their regular practice session and reported an RPE score (Borg CR-10 scale) immediately post-practice. The findings of this study reveal the presence of a strong significant relationship (r = 0.714) between Stress and RPE. However, weak non-significant relationships (r = 0.198-0.287) were observed between RPE and all jump-related metrics (Jumps, Jumps 15+, Jumps 20+, Average Jump Height) as well as Active Minutes (r = 0.330), indicating that an increase in internal load is more dependent on the type of activity that players perform rather than the duration of the practice session. Overall, these findings may help sports scientists and strength and conditioning practitioners detect changes in training load throughout a competitive season in male basketball players and ultimately improve the acute and chronic training-adaptation monitoring process.